(untitled) (Palimpsesto, 2022)
The article analyzes the trajectory of female labor informality in the pre- and post-pandemic scenario and records the social protection mechanisms that have emerged to face it from state action. For this, based on a descriptive statistical analysis that uses databases of the Chilean state, it investigates the possible changes that have occurred as a result of the health crisis. It is obtained that Chile presented indicators of female informality on the decline, which changes after the crisis associated with specific sociodemographic factors, among which the educational level stands out. This situation is especially complex as it accentuates the perennial gender gaps in Chile.